2016
DOI: 10.1007/s10668-016-9804-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of predicted sea level rise on land use/land cover categories of the adjacent coastal areas of Mumbai megacity, India

Abstract: Physical and ecological responses of the coastal areas in the vicinity of Mumbai, India, due to relative sea level rise are examined by different inundation scenarios. Evaluation of potential habitat loss under sea level rise was made by incorporating the land use/land cover (LULC) adopted from the digital elevation model with the satellite imagery. LULC categories overlaid on 1.0, 2.0, 3.0 and 4.0 m coastal elevation showed that the coastal areas of Mumbai were mostly covered by vegetation followed by barren … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 28 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…According to IPCC (2007) report, about 0.65 • C increase has been observed in global average surface temperature over last 50 years and is projected to increase by 1.1-6.4 • C. The rise in sea level has been observed with ongoing warming trend. Annual sea level rise between 2.5 and 3 mm along the coastline of Mumbai has been reported (Pramanik, 2017). Also, according to a study by NASA, this region has possessed increase in average temperatures by 2.4 • C for the period from 1881 to 2015 (NASA, 2015).…”
Section: Climate Changementioning
confidence: 99%
“…According to IPCC (2007) report, about 0.65 • C increase has been observed in global average surface temperature over last 50 years and is projected to increase by 1.1-6.4 • C. The rise in sea level has been observed with ongoing warming trend. Annual sea level rise between 2.5 and 3 mm along the coastline of Mumbai has been reported (Pramanik, 2017). Also, according to a study by NASA, this region has possessed increase in average temperatures by 2.4 • C for the period from 1881 to 2015 (NASA, 2015).…”
Section: Climate Changementioning
confidence: 99%
“…Mumbai is one of the world's most vulnerable cities to climate change (UN-Habitat 2010) and home to the largest population threatened by coastal flooding (IPCC-SREX 2012). At present, it experiences an annual sea level rise of between 2.5 and 3 mm along its coastline (Pramanik 2017). Sea level rise and the disappearance of natural buffer zones (e.g.…”
Section: Mumbaimentioning
confidence: 99%
“…Sea level rise and the disappearance of natural buffer zones (e.g. coastal wetlands) increase the threat from inundation, erosion and flooding of densely populated areas in the city, many of which lie only 2-3 m above mean sea level (Pramanik 2017;TERI 2014). Average sea level rise in the Mumbai region is projected to lie between 30 cm-80 cm until 2100 (TERI 2014) with sea surface temperatures increasing at 0.32°C per decade from 1985 to 1998 (Khan et al 2004).…”
Section: Mumbaimentioning
confidence: 99%
“…The single-value water surface method was used to find out the probable flooding for the various sea-level rise scenarios, and it is observed that the rate of coastal inundation is directly correlated with the sea-level rise (Singh and Kambekar 2017). Climate change-induced sea-level rise scenarios were used to study (Pramanik 2017) the impacts caused by these scenarios on the Mumbai coastal region and concluded that the sea-level rise can potentially reduce the drainage gradients in the city and can induce flooding conditions. For Kolkata city, climate change factors responsible for flooding in the region comprises the sea-level rise, extreme precipitation and storm surge.…”
Section: Climate Change Impacts and Flood Risksmentioning
confidence: 99%